Jejak Dualisme Pendidikan: dari Pendidikan Eropa hingga Pesantren di Awal Abad ke-20 - Muhamad Ihsan Khuluki; Renata Fifa Aulia; Fauziyah Zalfa Attazqiya; Sutrimo Purnomo (Pusat Riset dan Inovasi Nasional, 2026)
Educational dualism is a phenomenon that emerged in the Indonesian education system since the Dutch colonial era, which separated Western education from indigenous education. Western education introduced by the colonial government was more oriented towards colonial administrative and economic interests, and was generally intended for Europeans and indigenous elites such as the priyayi class. Meanwhile, indigenous communities widely developed religious-based education through Islamic boarding schools (pesantren) institutions that gave birth to communities of santri (Islamic students). This study aims to analyze the forms of educational dualism in the early 20th century by reviewing three developing educational models: European education, priyayi education, and santri education. The method used is a literature study by examining various books, scientific journals, and historical sources relevant to the development of education during the colonial period. The results of the study indicate that European education functioned as a means of developing an educated workforce that supported the colonial administration, while priyayi education became a path of social mobility for indigenous elites who acted as intermediaries between the colonial government and society. On the other hand, santri education through Islamic boarding schools developed independently and played an important role in maintaining religious values and the cultural identity of the community. Thus, the dualism of education during the colonial period not only reflected the inequality of access to education, but also shaped the social structure and intellectual dynamics of Indonesian society in the early 20th century.